Intrinsically High Magnetic Performance in Core–Shell Structural (Sm, Y)Fe12‐Based Permanent Magnets (Adv. Mater. 28/2022). Issue 28 (14th July 2022) - Zhao, Lizhong; Su, Rui; Wen, Lin; Li, Wei; Liu, Xiaolian; Zhang, Zhenhua; Zhao, Rongzhi; Han, Yuyan; Zhang, Xuefeng; Li, Wei
Abstract : (Sm, Y)Fe12 ‐Based Magnets In article number 2203503, Xuefeng Zhang, Wei Li, and co‐workers demonstrate the construction of a core–shell structure (Sm‐rich shell and Y‐rich core) in a (Sm, Y)Fe12 ‐based magnet via a spontaneous spinodal decomposition process, resulting in the synchronous enhancement of magnetic properties and phase stability in the optimized alloy. An innovative strategy is thus provided, which has important significance for the design of high‐performance magnets.